PELATIHAN PENDEKATAN PEMBELAJARAN MENDALAM (DEEP LEARNING) SEBAGAI SOLUSI PEMBELAJARAN MASA DEPAN BAGI GURU DI SDN 1 GULINGAN, BADUNG - I Komang Sukendra; I Made Subrata; I Made Surat; I Gusti Ayu Rai; Ni Made Pira Erawati (LP3M Universitas PGRI Mahadewa Indonesia, 2025)
The transformation of learning at the elementary school level requires teachers to apply instructional approaches aligned with 21st-century education demands, particularly Deep Learning–based instruction. However, preliminary observations indicated that most teachers at SDN 1 Gulingan, Badung still faced challenges in understanding the concepts, principles, and systematic implementation of deep learning in classroom practice. This community service program aimed to enhance teachers’ competencies in applying the Deep Learning approach through training, instructional design development, hands-on classroom implementation, and continuous mentoring. The implementation applied the Participatory Action Learning System (PALS) model consisting of five stages: socialization, theoretical and practical training, integration of technology to support learning, classroom mentoring, and program sustainability reinforcement through a professional learning community. The results demonstrated a significant improvement across four competency indicators: understanding of deep learning concepts (from 48% to 88%), ability to design lesson plans using the Deep Learning framework (from 42% to 81%), use of educational technology (from 55% to 90%), and classroom implementation of deep learning (from 38% to 82%). In addition, classroom observations during mentoring indicated a shift from teacher-centered to student-centered learning, characterized by increased collaborative, exploratory, and reflective student activities. The program also produced a sustainability outcome through the establishment of an Innovation-Based Teacher Working Group (KKG) as a platform for sharing best practices and continuous professional development. In conclusion, training and mentoring based on the PALS model proved effective in improving teachers’ pedagogical competence and fostering the implementation of innovative instructional practices aligned with future education demands.